The influence of green marketing on costumer loyalty of The Body Shop mediated by brand image - Indah Maharani Wulandari; Yunita Engriani (Marketing Management Studies, 2022)
This study intends to examine the impact of green marketing on The Body Shop customer loyalty in the city of Padang via brand image. All The Body Shop consumers that reside in the city of Padang make up the study's population. In this study, 154 respondents made up the samples. Data was gathered using a Google Form for an online survey, and SmartPLS 3.0 software was used to process the results. The study's findings show that green marketing has a significant impact on costumer loyalty, green marketing has a significant impact on brand image, brand image has a significant impact on costumer loyalty, and green marketing has a significant impact on customer loyalty through brand image.